Pre-Transplant Platelet Refractoriness and Alternative Donors Are Associated With Cytomegalovirus Retinitis in Hematopoietic Stem Cell Transplantation for Severe Aplastic Anemia - Zhang, Yuehong; Liang, Yuqin; Zhang, Xu; Wang, Shunqing; Cao, Jinpeng; Gao, Zongyin; Li, Ling; Mo, Wenjian (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Cytomegalovirus retinitis is a severe, vision-threatening opportunistic infection in an immunodeficient population. Reports on cytomegalovirus retinitis in hematopoietic stem cell transplant recipients due to severe aplastic anemia have been scant. This study assessed the risk of cytomegalovirus retinitis in relation to the pre-transplant status of severe aplastic anemia patients. Methods: We conducted a retrospective nested case-control study of cytomegalovirus retinitis among severe aplastic anemia patients receiving allogeneic hematopoietic stem cell transplants in a tertiary care institution that attends severe aplastic anemia patients from southern China from January 1, 2013 to December 31, 2018. Each cytomegalovirus retinitis case was matched with four controls without cytomegalovirus retinitis by age and gender. Thirteen pre-transplant parameters were chosen to compare the risk factor levels between the cases and controls. Multivariable logistic regressions were used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs). Results: A total of 361 severe aplastic anemia patients received hematopoietic stem cell transplants in the study period 2013–2018 in our medical institution, and 31 (8.58%) developed cytomegalovirus retinitis. Cytomegalovirus retinitis was diagnosed in the median of 148 days after transplantation. We confirmed platelet refractoriness more frequently in cases than in controls (p = 0.0005). Compared with human leukocyte antigen-matched sibling donors, alternative donors were significantly more prone to cytomegalovirus retinitis (p = 0.0009). After stepwise selection in multivariate logistic regression, platelet refractoriness (OR 5.41, 95% CI 1.98–15.39), haploidentical donor (OR 7.46, 95% CI 2.19–34.87), and unrelated donor (OR 8.38, 95% CI 2.30–41.34) were associated with an increased risk of cytomegalovirus retinitis. Conclusions: Pre-transplant platelet refractoriness and alternative donors were significant predictors of cytomegalovirus retinitis in severe aplastic anemia recipients. These results highlight the importance of accounting for existing risks while developing prevention strategies and preemptive treatment for severe aplastic anemia recipients. We recommend that the platelet count be closely monitored and thrombopoietin be properly applied during the period when cytomegalovirus retinitis is prone to occur.